The - West, Darrell M. (Bedford/St. Martin's, 2001)
Arguing against prevailing wisdom that the media's influenced has increase in the past decade, West cites current research and carefully selected case studies to support his controversial thesis. Covering over 200 years of American history, this brief text, with its lively case studies, will engage students at all levels